Implementation of HOTS-Based Learning Tools Through a Collaborative Learning Model by Applying the Merdeka Curriculum to Sixth Grade Students at SDN Lahuafu - Arfin, Arfan; Abdul Latief, Juraid; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to evaluate the implementation of learning tools that integrate Higher Order Thinking Skills (HOTS) with a collaborative learning model within the framework of the Merdeka Curriculum for sixth-grade students at SDN Lahuafu. This research uses a qualitative descriptive approach with data collection techniques including observation, interviews, questionnaires, and documentation. The results show that HOTS-based learning tools can be optimally applied in thematic learning, especially through activities that require students to think critically, such as group discussions, contextual problem-solving, and open-ended questions. Collaborative learning provides opportunities for students to actively work together in solving problems and sharing understanding reflectively. Supporting factors identified include student enthusiasm, teacher readiness as facilitators, and the flexibility of the Merdeka Curriculum. On the other hand, obstacles encountered include time constraints, disparities in student abilities, and limited learning resources. Overall, this implementation has proven effective in enhancing students’ active engagement, critical thinking skills, and the overall quality of learning.